Thermal degradation of turbine components in a military turbofan. (April 2022) - Szczepankowski, Andrzej; Przysowa, Radoslaw
Highlights: Successive stages of component degradation were tracked in service. Damage-tolerant maintenance approach was implemented for turbine components. Afterburner ignition system contributes to reduced life and thermal damage of components. Abstract: In gas-turbine engines, temporary variation of the temperature field in the turbine inlet causes thermal stress on the turbine components. In military engines, the afterburner is a source of additional stress to turbines, especially when it is activated. The aim of the study is failure analysis of the turbine components of the RD-33 turbofan, operated by the Polish Air Force. The results of visual inspection illustrate the critical condition of turbine blades and guide vanes. The sources of thermal and dynamic stress are analyzed. It is shown that the specific design of the afterburner activation system is a significant contributor to accelerated degradation of the turbine components and premature grounding of engines. After activating the afterburner, during the ignition and propagation of the flame, local overheating of the turbine components occurs and initiates their damage. To reduce the operating costs of the engine, actions limiting the negative impact of the afterburner on the turbine durability are proposed.